Frontiers of Economic Policy Communications - Stankova, Olga Ilinichna (Washington, D.C. : International Monetary Fund, 2019)
The paper provides an overall view of communications across various areas of economic policy, aiming to help country authorities as they increasingly use communications as a policy tool in its own right. The paper identifies frontier communications challenges, drawing on a large body of research on the salient issues. Although communications can never be a substitute for good policies, economic reforms are more likely to fail or even be reversed if they are not understood or accepted by those whom they affect.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet